Can circulating oxidative stress-related biomarkers be used as an early prognostic marker for COVID-19? - Uysal, Pelin; Yüksel, Arzu; Durmus, Sinem; Cuhadaroglu, Çaglar; Gelisgen, Remise; Uzun, Hafize (Frontiers in Medicine, 2023)
Background: Oxidative stress play an important role in the pathogenesis of many diseases. This study aimed to investigate the relationship between nuclear factor kappa B (NF-B) and oxidative stress and the severity of the disease in new COVID-19 patients; and, to compare the levels of NF-B, oxidized LDL (oxLDL) and lectin-like oxidized-LDL receptor-1 (LOX-1) with oxygen saturation, which is an indicator of the severity parameters of the disease in COVID-19 patients. Method In this prospective study, 100 COVID-19 patients and 100 healthy subjects were selected. Results: LOX-1, NF-B and oxLDL were found to be higher in COVID-19 patients compared to the healthy subjects (p <0.001 for all). According to the results of correlation analysis, it was found that there was no significant relationship between oxygen saturation and LOX-1, NF-B and oxLDL parameters. There was significant relationship between oxLDL with LOX-1 and NF-B in patients with COVID-19 disease. ROC analysis results of the highest discrimination power were oxLDL (AUC:0.955, CI:0.904-1.000; sensitivity: 77% and specificity: 100%, for cut off: 127.944 ng/L) indicating COVID-19. Conclusion: Oxidative stress plays an essential role in COVID-19. NF-B, oxLDL and LOX-1 seem to represent good markers in COVID-19. Our study also showed that oxLDL has the highest power in distinguishing patients with COVID-19 from the healthy subjects.